URGENSI RETORIKA SEBAGAI KETERAMPILAN BERBICARA DALAM MELAPORKAN HASIL OBSERVASI SISWA SMK - Puspitasari, Mega; Lutfitasari, Wevi; Rahman, Bohri (Jurnal Bahasa Indonesia Prima (BIP), 2023)
This research describes the rhetoric urgency in Observation reporting of covid-19 by Vocational High School students. Observations report requires interesting rhetoric or delivery techniques so listeners are informed, entertained, and influenced by the content conveyed. Research data is in the form of oral video recordings of student observation reports. The total of students studied was 70 people. Students collect videos through the e-learning application google classroom. Researchers observe and take notes to collect student rhetoric data. The results showed that 59% of students were good at reporting observations, and 41% of students were poor at reporting observations. This percentage is obtained from the accumulated value of the students' rhetorical strategy delivery technique, which consists of mastery of content, vocals (intonation and pronunciation), performance ( gestures and expressions), and language style. Students who score less are due to 1) a lack of confidence in reporting the results of observations that have been made, 2) vowel delivery techniques consisting of insufficient intonation and pronunciation, and 3) not utilizing body language forms of gestures and expressions.